Perancangan Wide Area Network (WAN) Dengan Teknologi Virtual Private Network (VPN) - Syarif hidayatulloh; Wahyudin Wahyudin (Universitas Bina Sarana Informatika, 2019)
The use of information technology and its use in collecting and processing data into information that is useful in decision making will play a role in determining the success of an organization or company in the future. This happened to PT. Jasa Cendekia Indonesia, the computer network that is owned has not met the needs of its employees. A good computer network is one that can serve sharing resources, data security, resources more efficiently and up-to-date information. Basically if a company can hold a computer network that serves the above for employees, of course it will make it easier for employees to do the work and improve the standards of the company itself. The proposed network built by the author for PT. Indonesian Scholar Services is a computer network built with Virtual Private Network technology. Because companies that have communication between the head office and branches that are good and safe, will be the capital for their companies in facing challenges in the era of globalization. Communication that is connected to a fast and secure computer network will make it easier for a company to supervise the activities of its company.